2020
DOI: 10.3389/fncel.2020.564106
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 and Glutamate Receptors Co-operate With Brain-Derived Neurotrophic Factor (BDNF) and TrkB to Modulate ERK Signaling in Adult Striatal Slices

Abstract: In the striatum, the input nucleus of the basal ganglia, the extracellular-signal-regulated kinase (ERK) pathway, necessary for various forms of behavioral plasticity, is triggered by the combined engagement of dopamine D1 and ionotropic glutamate receptors. In this study, we investigated the potential crosstalk between glutamatergic, dopaminergic, and brain-derived neurotrophic factor (BDNF)-TrkB inputs to ERK cascade by using an ex vivo model of mouse striatal slices. Our results confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Third, DA might activate or inactivate different signaling pathways that lead to opposite effects. DA has been shown to exert biological effects through various signaling pathways including cAMP/PKA pathway, AKT/GSK-3 β pathway, Wnt/ β -catenin pathway, and ERK pathway [ 36 39 ]. It was found that DA could enhance the osteogenic differentiation of BMSCs by modulating the ERK signaling pathway [ 14 ], whereas our results showed that DA suppressed the osteogenic differentiation of rBMSCs by modulating the AKT/GSK-3 β / β -catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Third, DA might activate or inactivate different signaling pathways that lead to opposite effects. DA has been shown to exert biological effects through various signaling pathways including cAMP/PKA pathway, AKT/GSK-3 β pathway, Wnt/ β -catenin pathway, and ERK pathway [ 36 39 ]. It was found that DA could enhance the osteogenic differentiation of BMSCs by modulating the ERK signaling pathway [ 14 ], whereas our results showed that DA suppressed the osteogenic differentiation of rBMSCs by modulating the AKT/GSK-3 β / β -catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF enhances neuronal survival and protects synaptic function by binding to tropomyosin receptor kinase B (TrkB) [ 33 , 34 ]. Simultaneously, BDNF promotes neuronal outward growth and recombination of dendritic spines, thereby improving neuronal connectivity [ 35 ]. NGF is a nerve cell growth regulator with dual biological functions of neuron nutrition and neurite outgrowth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated ERK as a coincident detector of D1R-mediated signaling and NMDA receptor activation in the striatum critical to the regulation of drugdependent synaptic plasticity in the striatum (Zhang et al, 2004;Valjent et al, 2005;Jiao et al, 2007;Bertran-Gonzalez et al, 2008;Fasano et al, 2009;Ren et al, 2010;Morella et al, 2020). For example, both NMDA and D1 antagonists have been shown to block ERK phosphorylation in the striatum in response to a variety of drugs of abuse (Valjent et al, 2000;Valjent et al, 2004;Valjent et al, 2005).…”
Section: Discussionmentioning
confidence: 99%